2021
DOI: 10.1093/ehjci/jeab101
|View full text |Cite
|
Sign up to set email alerts
|

Risk predicting for acute coronary syndrome based on machine learning model with kinetic plaque features from serial coronary computed tomography angiography

Abstract: Aims More patients with suspected coronary artery disease underwent coronary computed tomography angiography (CCTA) as gatekeeper. However, the prospective relation of plaque features to acute coronary syndrome (ACS) events has not been previously explored. Methods and results One hundred and one out of 452 patients with documented ACS event and received more than once CCTA during the past 12 years were recruited. Other 101 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 31 publications
0
11
0
Order By: Relevance
“…XGBoost represents a technical building set of trees in a progressive way on the loss of from weak decision tree base learners [ 19 ]. It can learn quickly and efficiently from large amounts of data and its great flexibility makes it possible to learn even from missing data [ 20 ]. The XGBoost model had a much higher predictive accuracy compared to the generalized linear model, being able to capture complex associations in the data without requiring explicit high-order interactions and non-linear functions [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…XGBoost represents a technical building set of trees in a progressive way on the loss of from weak decision tree base learners [ 19 ]. It can learn quickly and efficiently from large amounts of data and its great flexibility makes it possible to learn even from missing data [ 20 ]. The XGBoost model had a much higher predictive accuracy compared to the generalized linear model, being able to capture complex associations in the data without requiring explicit high-order interactions and non-linear functions [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies on CCTA multi-parameter models for prediction of MACE, 21,22 the multiple parameters usually included only CCTA stenosis and qualitative or quantitative characteristics but without FFRct. Few studies 23 reported on the three-kind multi-parameter model for predicting MACE. Still, TPV resulted as the significant quantitative parameter, and parameters such as LPVP were not included, which was an independent risk factor for predicting MACE.…”
Section: Discussionmentioning
confidence: 99%
“…An artificial intelligence deep-learning software prototype (DEEPVESSEL, KEYA Medical, China) was used to calculate FFRCT value in a manner that was blinded to the clinical findings according to the previous researches ( 12 , 13 ). It utilizes a deep learning algorithm to learn the complex mapping between FFR and the input features derived from the coronary artery anatomical data.…”
Section: Methodsmentioning
confidence: 99%